2017
DOI: 10.1097/md.0000000000008586
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of intravenous acetaminophen for pain control following total knee and hip arthroplasty

Abstract: Background:This meta-analysis aimed to evaluate the efficiency and safety of intravenous acetaminophen as an adjunct to multimodal analgesia for pain control after total joint arthroplasty (TJA).Methods:PubMed, Embase, Web of science, Medline, and Cochrane library databases were systematically searched. Randomized controlled trials (RCTs) and non-RCTs were included. Fixed/random effect model was used according to the heterogeneity tested by I2 statistic. Meta-analysis was performed using Stata 11.0 software.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 25 publications
(26 reference statements)
2
21
0
2
Order By: Relevance
“…Patients and their physicians often turn to surgical treatments to address progressive pain and disability, including arthroscopy and total knee arthroplasty (TKA) (Bonanzinga et al, 2018;Ro, Heo, & Lee, 2018). However, in 6 months after TKA, 16-39% of patients still sustain knee pain (Liang, Cai, Li, & Ma, 2017).…”
mentioning
confidence: 99%
“…Patients and their physicians often turn to surgical treatments to address progressive pain and disability, including arthroscopy and total knee arthroplasty (TKA) (Bonanzinga et al, 2018;Ro, Heo, & Lee, 2018). However, in 6 months after TKA, 16-39% of patients still sustain knee pain (Liang, Cai, Li, & Ma, 2017).…”
mentioning
confidence: 99%
“…One randomized, doubleblinded trial showed that patients receiving IV acetaminophen following TKA had better pain relief [11]. In another prospective study, Gupta et al [21] showed that IV acetaminophen significantly reduced patients' pain scores, a finding confirmed by multiple other authors [10,13]. In particular, administering IV acetaminophen intraoperatively may reduce pain in the immediate postoperative period [22].…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies of TJA patients receiving IV acetaminophen have demonstrated a reduced LOS, fewer adverse events [9], lower pain scores [10,11] and opioid requirements [11], and a decreased need for rescue opioids [12]. However, 2 recent meta-analyses have shown mixed results, citing limited quality evidence supporting the use of IV acetaminophen and the need for future randomized controlled trials [13,14]. In contrast, 2 recent prospective trials found modest improvements in pain and opioid consumption [18,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Матааналіз, проведений L. Liang та співавт. [17] показав, що внутрішньовенне введення парацетамолу значно знизило післяопераційні показники болю та зменшило використання опіоїдів після ендопротезування кульшового та колінного суглобів. За інформацією, поданою в спеціальній літературі, використання парекоксибу зменшує споживання морфіну приблизно на 30 % у перші 24 год після різних видів операцій [18,19].…”
Section: результати та їх обговоренняunclassified